(untitled) (The Pretoria Student Law Review, 2023)
The use of Facial Recognition Technologies (FRT) has become increasingly prevalent. While these technologies have been applauded for their many benefits, their use have been criticised for problems relating to accuracy. More particularly, FRT technologies have demonstrated low accuracy when identifying people of colour. This has led to the call for diversification of data, which has been intensified by major corporations and nations competing to lead in Artificial Intelligence development (the AI race). In an attempt to diversify its data sets, China, as a significant player in the AI race, has entered into an agreement with Zimbabwe. The agreement is meant to benefit both parties mutually as a ‘win-win’ agreement, which entails the collection of African facial IDs in exchange for high-end mass surveillance technologies. This article questions whether this agreement can genuinely be a win-win. To demonstrate this, the article will discuss and analyse China’s viewpoint on this ‘win-win’ in light of the AI race and take a closer look at how this agreement places China one step ahead of others in the race to lead facial recognition technologies. As such, the article examines that which is hidden in China’s win-win perspective by delving deeper into the biometric data and the underlying principles of its Regulation to determine whether the collection of Facial IDs is in line with these principles. Finally, I attempt to redefine the meaning of what is truly a ‘win-win’ in this context.